2013
DOI: 10.5935/1678-9741.20130010
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies after heart transplantation: psychological implications

Abstract: Objectives: To investigate coping strategies used by patients submitted to heart transplantation and whether they are related to the perception of the disease and transplantation.Methods: Cross-sectional study with quantitative and qualitative analysis. The sample of 32 patients was assessed by the Ways of Coping Scale and socio-demographic questionnaire, and five of them were selected for interviews. The internal consistency of the scale was assessed, the variables and strategies involved were crossed and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
(30 reference statements)
1
14
0
2
Order By: Relevance
“…A study carried out in a hospital in Belo Horizonte, which investigated the demographic and epidemiological profile of patients undergoing a heart transplant, observed a predominance of male patients, living in cohabitation, with incomplete primary education and retirees. The average age range of 53 years can also be observed in other studies on the subject [2,7,13,14] .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A study carried out in a hospital in Belo Horizonte, which investigated the demographic and epidemiological profile of patients undergoing a heart transplant, observed a predominance of male patients, living in cohabitation, with incomplete primary education and retirees. The average age range of 53 years can also be observed in other studies on the subject [2,7,13,14] .…”
Section: Discussionsupporting
confidence: 65%
“…When a cardiopathy occurs, a complex interaction of variables interferes in the progression and patient's recovery [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Trevizan et al 48 heart transplantation per se is already a predictor of QoL improvement for transplant patients because they feel satisfied due to overcoming the pre-transplant difficulties. 49 Likewise, other studies have shown that HT surgery in patients with refractory heart failure presents better results in relation to QoL, as they see an improvement in the physical condition. 50,51 The results obtained in the present study show that the exercise protocol in water increased the QoL improvement.…”
Section: Quality Of Lifementioning
confidence: 93%
“…It has been found that CHD also affects emotional, mental, social, and economic conditions of the patients. In other words, heart injuries, not only create physical symptoms and disabilities, but also have a harmful effect on the mental state of a person dealing with it, and may result in psychological stresses such as death depression, death anxiety and coping style dysfunction (3,4).…”
Section: Introductionmentioning
confidence: 99%